Cation-exchange synthesis of PbSe/ZnSe hetero-nanobelts with enhanced near-infrared photoelectronic performance. (28th May 2021) - Kang, Ping; Zheng, Kai-Ge; Wang, Zhuo; Chen, Li; Guo, Zheng
Abstract: To develop excellent photoelectronic and photovoltaic devices, a semiconductor with high photoelectron production efficiency and broad band absorption is urgently required. In this article, novel II-type PbSe/ZnSe hetero-nanobelts with enhanced near-infrared absorption have been synthesized via a facile strategy of a partial cation-exchange reaction and thermal treatment. Derived from ZnSe·0.5N2 H4 nanobelts as templates, the belt-like morphology was preserved. Due to the mismatch of the crystal type and parameters between PbSe and ZnSe, the formed PbSe in the form of nanoparticles were separated out and decorated on the nanobelts. Furthermore, the composition ratio of Pb/Zn can be tuned through manipulating the adding amount of Pb 2+ cations, the reaction temperature and time. The ultraviolet−visible−infrared diffuse spectra measurements suggest that the as-prepared PbSe/ZnSe hetero-nanobelts exhibited a broad band absorption from 300 to 1000 nm. In addition, they demonstrated excellent photoresponsivity in the same wavelength region and displayed a peak at approximately 840 nm. Finally, the enhanced photoelectronic sensing mechanism was discussed.